Makna Simbolis Bahasa Kiasan dalam Antologi Puisi “Selamat Menunaikan Ibadah Puisi” Karya Joko Pinurbo (International Forum of Researchers and Lecturers, 2025)
This study focuses on the symbolic meanings embedded in the use of figurative language in the poetry anthology Selamat Menunaikan Ibadah Puisi by Joko Pinurbo. The research utilizes a descriptive qualitative approach, with semiotic analysis serving as the theoretical foundation. The purpose of this study is to examine how the figurative language used in the poems contributes to conveying deeper symbolic meanings, beyond their role as mere rhetorical devices. The findings of this research reveal that the figurative language within the poems plays a significant symbolic role in expressing complex themes such as inner suffering, memories, identity, alienation, and the quest for the meaning of life. Symbols like 'storm,' 'refrigerator,' 'dusk,' 'window,' 'door,' 'river,' and others are employed to represent abstract concepts, providing a more nuanced understanding of the human experience. The study identifies various types of figurative language, including metaphor, simile, personification, hyperbole, synecdoche, paradox, and irony. Each of these elements serves to enrich the meaning of the poems, adding layers of depth to the interpretation and enhancing the aesthetic experience for the reader. Through these figurative expressions, the poet effectively invites the reader to engage with both the emotional and intellectual dimensions of the poetry. This research emphasizes how Joko Pinurbo's use of figurative language transcends its traditional ornamental function, making it a powerful tool for conveying complex symbolic and existential themes. By analyzing the symbolic meanings in the poems, this study contributes to a deeper appreciation of the interplay between language, meaning, and emotion in contemporary Indonesian poetry.